water element effect In the history of the Crusades in the Levant bilad alshaam (Journal of the College of Basic Education, 2024)
The Crusaders have erealized since the yset foot in the Levant in the late eleventh century AD Fifth Hijri , the need to preserve different water sources And the multiplicity in the region, especially in the parts they occupied, and is represented in Edessa and Antioch Beit Al-Maqdis , and Tripoli, and in order for their presence there to continue, it is necessary to strive towards subjugating the headwaters of theRivers or their estuaries. And depriving Muslims - as much as possible - of enjoying the advantages of the vital strategic water site